Pembuatan gigitiruan jembatan anterior pada lingir alveolar yang resorpsi Making anterior denture bridge on resorpted alveolar ridge - Aprillia Adenan; Taufik Sumarsongko (DiscoverSys Inc., 2012)
Bridge is a partial denture that attached permanently to the abutment, to replace missing natural teeth. It is easy tomake GTJ on normal elveolar ridge. But if the alveolar have already resorpted, pontik form need to be modified tomake artificial gingiva to look aesthetic. This paper reported the case of a 40-year-old man that has lost tooth 21and 22 for eight years. For two last years ago he used a removable denture. Patients feel uncomfort and lesssatisfied, so he wanted to made a new denture, a fixed denture and more comfortable. After intra oral andradiographic examination, conventional metal ceramics made on 11, 21, 22, 23 with the abutments at 11 and 23, aswell as pontik 21 and 22 and the addition of artificial gingiva in the area resorption. The bridge was seen aesthetic.